As virtualidades da lei 5692/71 para uma educação democratica e os pressupostos que dificultam sua implementação - Chagas, Maria do Céu Cavalcante (1978)
For seven years since the ru1es and bases estab1ished for 1st and 2nd grade teaching v have been in force, their imp1ementation ' has been subject to severa1 practical and administrative hindrances due tri severa1 degrees of acceptance by society of the innovations brought about by Law, especia11y with regard to professiona1is;ng education, which is the most controverted aspect of the Reform. lhe period extending from the promu1gation of Law 5692/71 to the present days has been characterized more by oposition to changes than by the adoption of such changes by the educationa1 system.